Canteen Service Quality and Student Satisfaction: A Case Study of a Private College in Kathmandu - Chand, Dilisha (Nepalese Journal of Hospitality and Tourism Management, 2025)
The paper examines the quality of the service of the canteen and satisfaction level of students from the canteen operating within a private college of Kathmandu. Hence, the study conducted the survey among the 106 students studying different courses at the sampled college. The study used a mean analysis and a correlation coefficient as a data analytical tool. The study revealed a moderate to below-average satisfaction among students regarding the canteen services. The study concluded that tangibility significantly influences student satisfaction while physical facilities, equipment, and appearance are other key factors. Responsiveness and reliability also made an impact on student satisfaction towards college canteen services. However, reliability, empathy, and assurance have weaker impact on students’ satisfaction as well, indicating even their importance in college canteen services.